Gaya Bahasa Sindiran Netizen dalam Kolom Komentar Akun @fujiiian di Aplikasi TikTok - Syamsuddin, Muderika; Mayong, Mayong; Wijayanti, Tuti (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to identify the form and function of satire language style in netizen comments on the TikTok account @fujiiian. This type of research is descriptive qualitative research. The source of research data, namely netizen comments in the comments column of the @fujiiian account on the TikTok application. Data collection techniques are carried out using observation and documentation techniques or screen capture. Data analysis techniques, namely data reduction to highlight relevant information, data presentation is the stage where the data is displayed to be more easily understood, and conclusions to summarize the data that has been analyzed to be associated with the focus of the study. The results of this study indicate that the form of language style includes irony, cynicism, and sarcasm. The function of satire language style is divided into 5 categories, namely functions in the form of sentences, opinions, questions, similarities, comparisons, and commands.